2016
DOI: 10.1111/emr.12193
|View full text |Cite
|
Sign up to set email alerts
|

Germination of native and introduced plants from scats of Fallow Deer (Dama dama) and Eastern Grey Kangaroo (Macropus giganteus) in a south‐eastern Australian woodland landscape

Abstract: Summary Introduced deer occur in many forests and woodlands in Australia and potentially play an important role in influencing the floristics and structure of these landscapes through eating plants and disseminating seeds. In a glasshouse trial, we tested whether field‐collected scats of Fallow Deer (Dama dama) contained viable plant seeds. Scats of deer obtained from a woodland study area in Kosciuszko National Park, New South Wales, produced seedlings from a range of native and introduced plant species. Forb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Fallow deer ( Dama L.) and grey kangaroo ( Macropus giganteus Shaw) also consume C. helmsii to some extent Claridge et al (). Outside its native range, no known herbivory exists beyond generalist grazing by livestock if present.…”
Section: Herbivory and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Fallow deer ( Dama L.) and grey kangaroo ( Macropus giganteus Shaw) also consume C. helmsii to some extent Claridge et al (). Outside its native range, no known herbivory exists beyond generalist grazing by livestock if present.…”
Section: Herbivory and Diseasementioning
confidence: 99%
“…In its native range, it has been shown that C. helmsii can be dispersed by fallow deer Dama dama and grey kangaroo Macropus giganteus through examination of scats (Claridge, Hunt, Thrall, & Mills, 2016). Wildfowl and livestock, such as highland cattle and New Forest ponies, are considered suitable vectors for fragmented stem and node sections of C. helmsii in Britain (Denys, Packet, Jambon, & Scheers, 2014;Ewald, 2014;Smith, 2015).…”
Section: Seed Production and Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaden worden zowel verspreid door water, als via de vacht en poten van dieren (Thorsen et al 2009) en wellicht ook na indigestie door allerlei dieren (Denys et al 2014a). Claridge et al (2016) verkregen kiemlingen uit de uitwerpselen van damherten en kangoeroes. Ook via schoeisel en materiaal dat gebruikt wordt bij beheerwerken kunnen zaden verspreid worden; elk transport van grond of planten van besmette plaatsen naar geschikte groeiplaatsen komt hiervoor eveneens in aanmerking (cf.…”
Section: Generatiefunclassified
“…2010; Claridge et al . 2016), impacts to agricultural and forestry production and infrastructure (Putman & Moore 1998; Lindeman & Forsyth 2008), carrying diseases that can affect other species or drinking water catchments (Burgin et al . 2015; Davis et al .…”
Section: Introductionmentioning
confidence: 99%